Matchmaking Bureau at the Ministry of Religious Affairs of Surakarta: The Legal Utilitarianism Perspective on the Samawa Program - Utami, Ria Cahyaning; Hilmy, Ahmad Arif Masdar; Al Adawiyah, Mutiah Robiah (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
Non-governmental entities often facilitate current matchmaking trends, promoting certain ideologies that may contradict the Islamic family law model introduced by the state. In response, Surakarta’s Ministry of Religious Affairs launched the